cAMP mediated regulation of fibroblast to myofibroblast differentiation in idiopathic pulmonary fibrosis - Wright, Rebecca (2016)
Idiopathic pulmonary fibrosis (IPF) is a fibrotic lung disease with no effective treatment. Myofibroblasts contribute to the pathology of IPF by secreting large amounts of extracellular matrix proteins such as alpha smooth muscle actin (α-SMA) and Collagen I (Col 1). Myofibroblasts have reduced Prostaglandin E2 (PGE2), a key anti-fibrotic mediator, due to diminished cyclooxygenase-2 (COX-2) expression.